Multidisciplinary Pulmonary Embolism Response Team (PERT) a propensity score matched single centre experience from Germany. (3rd May 2023) - Sagoschen, I; Scibior, B; Farmakis, I T; Munzel, T; Keller, K; Konstantinides, S; Hobohm, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Over the last years, the concept of multidisciplinary pulmonary embolism response teams (PERTs) has emerged to encounter the increasing variety and complexity in the management of acute pulmonary embolism (PE). Purpose: To investigate the composition and added clinical value of PERT in our city. Methods: Over a 5-year period (01/2017-09/2022), patients with confirmed PE were enrolled in a prospective single-centre cohort study (PERT). We investigated the composition of PERT and compared, after propensity score matching, patients with acute PE prior and after the formation of PERT at our institution. The primary outcome was in-hospital PE-related mortality before and after the formation of PERT. Results: During the period from 2017 to 2022, 88 patients with acute PE with a PERT decision were registered. Of those, 13 (14.8%) patients died during the in-hospital stay. Patients evaluated by a PERT had a mean age of 68 years; among these 48.9% were females, and 21.7% suffered from malignancy. Right ventricular dysfunction was present in 84.9% of the patients. In total, 42.0% were classified as intermediate-risk PE and 11.6% as high-risk PE. First PERT contact originated mostly by emergency departments (33.3 %) and intensive care unit (30.0%), followed by chest pain unit (21.3%) and regular ward (12.0%) (Figure 1a). The participation rate of specialties demonstrated that cardiologists (100%) or cardiac/vascular surgeons (98.6%) were included in almost all PERT activations followed by radiologist (95.9%) or anesthesiologist (87.8%). Further disciplines were present in few cases as summarized in Figure 1b. When comparing patients characteristics of the pre-PERT era with the PERT era, more patients were classified as sPESI ≥1 and as high-risk according to ESC 2019 guidelines in the pre-PERT era (78.4% and 18.2%) opposed to the PERT era (71.6 and 11.4%) (Figure 2). A considerable higher all-cause mortality (31.8% vs. 14.8%) and PE-related mortality rate (22.7% vs. 13.6%) was observed in patients in the pre-PERT era compared to the PERT era. After propensity matching (1:1) by including parameters as age, sex, sPESI and ESC risk classes, an univariate regression analyses demonstrated, that the PE management based on a PERT-decision was associated with lower risk of all-cause mortality (OR, 0.37 [95%CI 0.18-0.77]; p=0.009) and PE-related mortality (OR, 0.54 [95%CI 0.24-1.18]; p=0.121) compared to patients without a PERT-decision. Conclusion: PERT implementation tended to reduce the mortality rate in patients with acute PE. Large prospective studies are needed to further explore the impact of PERTs on clinical outcomes.